Studying visual literacy: Research methods and the use of visual evidence. (June 2020) - Matusiak, Krystyna K.
The proliferation of images and their increased use in academic and everyday information practices has sparked an interest in visual literacy as an area of research and library instruction. Teaching approaches and student learning are examined using a variety of research methods and utilizing images in the research process. This paper provides a review of research methodology adopted in empirical studies of visual literacy that were published in academic journals between 2011 and 2017. The results indicate that one third (33%) of the examined studies adopted a quantitative approach with surveys being the most popular strategy. Qualitative and mixed-methods studies were a minority but represented a greater variety of strategies and data collection techniques. One third (33%) of the studies in the sample did not report any research methodology. Most of the studies (87%) used visual evidence in the research process.